Recurrent coma and fever in familial hemiplegic migraine type 2. A prospective 15-year follow-up of a large family with a novel ATP1A2 mutation. (July 2017) - Pelzer, N; Blom, DE; Stam, AH; Vijfhuizen, LS; Hageman, ATM; van Vliet, JA; Ferrari, MD; van den Maagdenberg, AMJM; Haan, J; Terwindt, GM
Background: Familial hemiplegic migraine (FHM) is a rare monogenic migraine subtype characterised by attacks associated with transient motor weakness. Clinical information is mainly based on reports of small families with only short follow-up. Here, we document a prospective 15-year follow-up of an extended family with FHM type 2. Patients and methods: After diagnosing FHM in a patient with severe attacks associated with coma and fever, we identified eight more family members with FHM and one with possible FHM. All family members were prospectively followed for 15 years. In total 13 clinically affected and 21 clinically non-affected family members were genetically tested and repeatedly investigated. Results: A novel p.Arg348Pro ATP1A2 mutation was found in 14 family members: 12 with clinical FHM, one with psychomotor retardation and possible FHM, and one without FHM features. In 9/12 (75%) family members with genetically confirmed FHM, attacks were severe, long-lasting, and often associated with impaired consciousness and fever. Such attacks were frequently misdiagnosed and treated as viral meningitis or stroke. Epilepsy was reported in three family members with FHM and in the one with psychomotor retardation and possible FHM. Ataxia was not observed. Conclusion: FHM should be considered in patients with recurrent coma and fever.